Rad recycled art - Kington, Emily, 1961- (Hungry Tomato, 2019)
"Turn everyday waste into a work of art! Design a futuristic cardboard building, make funky chicken bookends, and construct a robot from nuts. Readers will learn how to think outside of the box and create while recycling"--
Rad recycled art -- Top tips -- Materials -- Method -- Decoration and useful items -- Secret cat -- Wall mask -- Cardboard city -- Fish and tops -- Totem pole -- Notice board organiser -- Party bowls -- Paintbrush pals.
Includes bibliographical references and index.
Ages 8-12.
Grades 4-6.
Keywords: Handicraft -- Juvenile literature; Salvage (Waste, etc.) -- Juvenile literature; Found objects (Art) -- Juvenile literature; Handicraft; Recycling; Waste products